FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PEGAWAI DI BANK KONVENSIONAL JAKARTA BARAT - ahmad azmy (Universitas Lancang Kuning, 2019)
This study discusses how to improve kepuasan pegawaiin achieving work targets. The banking industry must provide excellent service to customers. Employees are the frontline in providing the best service to customers. The research object took one of the banks in West Jakarta. The process of collecting data in the form of questionnaires and distributed to 100 respondents. The dimensions used include compensation, work environment, leadership, supervisor relations, and training, development & resources. The results of the study show that the dimensions that have the highest relationship are job environment. The dimension that has the lowest relationship is compensation. The conclusions from this study prove that companies must create a safe and comfortable work environment. It aims to increase employee productivity. The compensation dimension is not a major concern in employee satisfaction. This shows that the work environment is very influential on kepuasan pegawaiin providing excellent service to customers.